Anisotropy-induced directional self-transportation of low surface tension liquids: a review. Issue 66 (7th November 2020) - Soltani, Mohammad; Golovin, Kevin
Abstract : The passive transportation of liquids is comprehensively reviewed specifically for low surface tension fluids. Abstract : Inspired by natural surfaces such as butterfly wings, cactus leaves, or the Nepenthes alata plant, synthetic materials may be engineered to directionally transport liquids on their surface without external energy input. This advantageous feature has been adopted for various mechanical and chemical processes, e.g. fog harvesting, lubrication, lossless chemical reactions, etc. Many studies have focused on the manipulation and transport of water or aqueous droplets, but significantly fewer have extended their work to low surface tension (LST) liquids, although these fluids are involved in numerous industrial and everyday processes. LST liquids completely wet most surfaces which makes spontaneous transportation an active challenge. This review focuses on recently developed strategies for passively and directionally transporting LST liquids.